Building the Benedict option : a guide to gathering two or three together in His name - Libresco, Leah (Ignatius Press, 2018)
"Building the Benedict Option is a combination spiritual memoir and practical handbook for Christians who want to build communities of prayer, socialization, and evangelization in the places where they live and work. Beginning when the author was a new convert, she desired more communal prayer and fellowship than weekly Mass could provide. She surveyed her friends--busy, young, urban professionals like herself--and created enriching or supportive experiences that matched their desires and schedules. The result was a less lonely and more boisterous spiritual and social life. No Catholic Martha Stewart, Libresco is frank about how she plans events that allow her to feed thirty people on a Friday night without feeling exhausted. She is honest about the obstacles to prayer and the challenge to make it inviting and unobtrusive. Above all, she communicates the joy she has experienced since discovering ways to open her home (even when it was only a small studio apartment). The reader will close this book with four or five ideas for events to try over the next few weeks, along with the tools to make them fruitful. From film nights to picnics in the park to resume-writing evenings, there are plenty of ideas to choose from and loads of encouragement to make more room in one's life for others."--Inside flap.